ALINHAVOS PARA UMA COSTURA: “BOITEMPO” - Souza, Raquel (Organon, 2012)
The autobiographical poetry of Carlos Drummond de Andrade, the threevolumes os Boitempo, Boitempo II (the old boy) and Boitempo III (forget to remember),point to the moderns autobiographic person constitution as a dialectical tensionbetween the contraries. Following the oximoro the poet builds his possiblesidentities to arrive at the self knowledge.